2016
DOI: 10.1371/journal.pone.0145908
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Differential Gel Electrophoresis to Identify Protein Biomarkers in Amniotic Fluid of Edwards Syndrome (Trisomy 18) Pregnancies

Abstract: BackgroundEdwards syndrome (ES) is a severe chromosomal abnormality with a prevalence of about 0.8 in 10,000 infants born alive. The aims of this study were to identify candidate proteins associated with ES pregnancies from amniotic fluid supernatant (AFS) using proteomics, and to explore the role of biological networks in the pathophysiology of ES.MethodsAFS from six second trimester pregnancies with ES fetuses and six normal cases were included in this study. Fluorescence-based two-dimensional difference gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In accordance with the results of the current study, the previous longitudinal study by Liong et al showed that VDBP is detectable in the CVF of all pregnant women during the second half of pregnancy, with no change in the CVF VDBP level between 20 and 35 weeks’ gestation [ 15 ], suggesting that VDBP is a physiologic constituent of the lower genital tract fluid. In addition, VDBP has been previously identified in the AF of pregnant women [ 19 ], and our preliminary experiment to determine the dilution ratio showed that VDBP levels in the AF without intra-amniotic infection were approximately 10 times higher than the levels in the CVF (supplementary materials). Similarly, the VDBP levels reported in pregnant maternal serum were 1000 times higher than those measured in the CVF in the current study [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 86%
“…In accordance with the results of the current study, the previous longitudinal study by Liong et al showed that VDBP is detectable in the CVF of all pregnant women during the second half of pregnancy, with no change in the CVF VDBP level between 20 and 35 weeks’ gestation [ 15 ], suggesting that VDBP is a physiologic constituent of the lower genital tract fluid. In addition, VDBP has been previously identified in the AF of pregnant women [ 19 ], and our preliminary experiment to determine the dilution ratio showed that VDBP levels in the AF without intra-amniotic infection were approximately 10 times higher than the levels in the CVF (supplementary materials). Similarly, the VDBP levels reported in pregnant maternal serum were 1000 times higher than those measured in the CVF in the current study [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 86%
“…In accordance with the results of the current study, the previous longitudinal study by Liong et al showed that VDBP is detectable in the CVF of all pregnant women during the second half of pregnancy with no change in the CVF VDBP level between 20 and 35 weeks' gestation [14] suggesting that VDBP is a physiologic constituent of the lower genital tract fluid. In addition, VDBP has been previously identified in the AF of pregnant women [8] and on other experiment to determine the dilution ratio showed that VDBP levels in the AF without intra-amniotic infection were approximately 10 times higher than the levels in the CVF (supplementary materials) [12] . Similarly, the VDBP levels reported in pregnant maternal serum were 1000 times higher than those measured in the CVF in the current study [3] .…”
Section: Discussionmentioning
confidence: 92%
“…MALDI‐TOF MS analysis was performed as a previous study . Pancreatin was used to calibrate ABI 4800M MALDI MS analyzer equipped with a 200 Hz 366 nm N 2 laser.…”
Section: Methodsmentioning
confidence: 99%
“…MALDI-TOF MS analysis was performed as a previous study. 8 Pancreatin was used to calibrate ABI 4800M MALDI MS analyzer equipped with a 200 Hz 366 nm N 2 laser. The MALDI-TOF MS test was performed at a mass range of 700 to 3200 Da (best mass range at 1500 Da).…”
Section: Maldi-tof Ms Analysismentioning
confidence: 98%